Postmodern use of the Bible the emergence of reader-oriented criticism - McKnight, Edgar V. (Nashville, TN Abingdon, 1988)
Includes bibliographical referensces and indexes.
Keywords: Bible -- hermeneutics; Bible -- criticism, interpretation, etc -- history -- 20th century; Postmodernism (Bible).